الصورة الذهنية للمؤسسة العمومية الاستشفائية خلال فترة كوفيد دراسة على عينة من الجمهور الخارجي لمستشفى رزيق البشير – بوسعادة - - عبير, بشيري; شريخ, سهيلة (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2021)
تهدف هذه الدراسة إلى معرفة واقع الصورة الذهنية لدى الجمهور الخارجي لمستشفى رزيق البشير ببوسعادة أثناء فترة لكوفيد19, ولوقوف على أهم العوامل المشكلة لها وأهم الوسائل الاتصالية المساهمة في بناءها, وتعتبر دراسة وصفية تستند على المنهج المسحي, وقد شملت ثلاث إطارات أساسية تتمثل في: الإطار المنهجي الذي تضمن مختلف الإجراءات المنهجية بداية بتحديد الإشكالية المتمحورة في تساؤل عام – ما هو واقع الصورة الذهنية للمؤسسة العمومية الاستشفائية العمومية (مستشفى رزيق البشير ) خلال فترة كوفيد 19 ?.أما الإطار النظري وتتضمن ثلاث فصول الأول تتطرق إلى الصورة الذهنية وأهم أساسيتها, أما الثاني تناول المؤسسة العمومية الاستشفائية وأهم العناصر المتعلقة بها, أما الثالث فتناول فيروس كورونا المستجد واهم العناصر المتعلقة بها, أما الإطار التطبيقي فقد شمل التعريف بمستشفى رزيق البشير, عرض وتحليل بيانات نتائج الدراسة. وخلصت الدراسة إلى أن اغلب المبحوثين راضون بشكل حسن على خدمات مستشفى رزيق البشير خلال فترة كوفيد 19, وان التعامل المباشر مع المستشفى أهم عوامل تشكيل الصورة الذهنية, إضافة إلى الإذاعة ومواقع التواصل الاجتماعي, ويرى الجمهور ضرورة تحسين خدمات مستشفى رزيق البشير أكثر خصوصا في فترة كوفيد19, وبناء وتحسين صورته الذهنية الداخلية أي ما يتم تقديمه إلى المستشفى من خدمات للجمهور الخارجي. This study aims to know the reality of the mental image of the external public of Raziq Al-Bashir Hospital in Bousaada during the period of Covid 19, and to find out the most important problem factors for it and the most important communication means contributing to its construction. It is considered a descriptive study based on the survey method, and it included three basic frameworks represented in: The methodological framework Which included various methodological procedures, beginning with defining the problem centered in a general question - what is the reality of the mental image of the public hospital public institution (Rizek Al-Bashir Hospital) during the period of Covid 19?. As for the theoretical framework, it includes three chapters, the first deals with the mental image and its most important basics, while the second dealt with The public hospital institution and the most important elements related to it, while the third dealt with the emerging corona virus and the most important elements related to it. As for the applied framework, it included the definition of Raziq Al-Bashir Hospital, presentation and analysis of data from the results of the study. The study concluded that most of the respondents are well satisfied with the services of Raziq Al-Bashir Hospital during the Covid 19 period, and that direct interaction with the hospital is the most important factor in shaping the mental image, in addition to radio and social networking sites, and the public sees the need to improve the services of Raziq Al-Bashir Hospital more, especially during the Covid 19 period. Building and improving its internal mental image, i.e. the services provided to the hospital for the external public.
Keywords: الصورة الذهنية – المؤسسة العمومية الاستشفائية – مستشفى رزيق البشير – وسائل الإعلام – سمعة المؤسسة – كوفيد 19. mental image - public hospital institution - Raziq al-Bashir Hospital - media - reputation of the institution - Covid 19.